"GRASS" ROOTS IN TEXAS: A Multiple Streams Approach to Understanding the Marijuana Movement's Policy Impact. (March 2017) - Harris, Katharine Neill; Morris, John C.
Several scholars have pointed to a gap between the social movement and policy literatures, and argue that the failure of each field to incorporate the other creates a missing link in our understanding of how social movements and policy shape each other. This study provides an opportunity to make these links by applying John Kingdon's multiple streams framework of agenda setting to the marijuana movement in Texas. Texas, an unlikely candidate for marijuana reform, was the site of sustained efforts to change marijuana laws during the 2015 legislative session. This research offers evidence about the ways in which social movements influence the policy process, and how the policy process responds to activist efforts. We find that despite well-organized movement efforts, political influence was limited. We argue that the reform movement's inability to control activist participation presents additional challenges in a nonballot initiative state such as Texas.